Bungong Rencong: Representation of the Fighting Spirit of Inong Balee in Aceh into Dance Creation - Cufara, Dwindy Putri; Gusmanto, Rico (Gondang: Jurnal Seni dan Budaya, 2024)
Inong Balee was Aceh's war fleet led by Indonesia's first female admiral, Keumalahayati. Inong Balee consisted of widows who lost theirhusbands in the war and girls who fought against the invaders. The progress of this fleet is represented as a Lioness standing proudly on the ship of the Sultanate of Aceh. This work emerged from the fighting spirit of heroic women. This Inong Balee spirit influenced the emancipation of Acehnese women. This is what makes Aceh women different from women in other regions, where Aceh women are known to have a tough nature.This spirit is interestingly implemented in the form of abstract dance artworks. The purpose of this research is to create an abstract dance artwork that represents the Lioness in the fighting spirit of Inong Balee in Aceh as a pioneer of emancipation. The method used is the creation method byAlma Hawkins which consists of exploration, improvisation, and formation. This research is expected to answer global challenges related to women's issues, especially women in social status. With the achievement of the objectives of this research, the research output can be targeted, namely a dance artwork entitled Bungong Rencong, a scientific article in an accredited national journal, and a copyright certificate for the artwork.